2015
DOI: 10.1002/jcsm.12048
|View full text |Cite
|
Sign up to set email alerts
|

SARC-F: a symptom score to predict persons with sarcopenia at risk for poor functional outcomes

Abstract: BackgroundA brief, inexpensive screening test for sarcopenia would be helpful for clinicians and their patients. To screen for persons with sarcopenia, we developed a simple five‐item questionnaire (SARC‐F) based on cardinal features or consequences of sarcopenia.MethodsWe investigated the utility of SARC‐F in the African American Health (AAH) study, Baltimore Longitudinal Study of Aging (BLSA), and National Health and Nutrition Examination Survey (NHANES). Internal consistency reliability for SARC‐F was deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
581
2
61

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 822 publications
(656 citation statements)
references
References 27 publications
12
581
2
61
Order By: Relevance
“…For such tools to become more commonplace, healthcare professionals need to be educated on the importance of sarcopenia and SO and how to incorporate routine screening and intervention for these conditions into their clinical practice. For example, screening for sarcopenia could be included as part of the Welcome to Medicare and annual Medicare wellness preventive exams using simple screening tools such as the SARC-F screen for sarcopenia [46].…”
Section: Discussionmentioning
confidence: 99%
“…For such tools to become more commonplace, healthcare professionals need to be educated on the importance of sarcopenia and SO and how to incorporate routine screening and intervention for these conditions into their clinical practice. For example, screening for sarcopenia could be included as part of the Welcome to Medicare and annual Medicare wellness preventive exams using simple screening tools such as the SARC-F screen for sarcopenia [46].…”
Section: Discussionmentioning
confidence: 99%
“…A score ≥ 4 points is reported to be predictive for sarcopenia and could be the trigger for a more detailed assessment of positively evaluated subjects [18] . The SARC-F questionnaire is so far one of the best available tools to screen for sarcopenia in routine medical practice, and its validity has already been proven in late-middle aged and elderly patients [19,20] . In order to get more information about muscle function, hand-grip tests are frequently performed and recommended [21] .…”
Section: Anthropometric Datamentioning
confidence: 99%
“…There is also interest in using questionnaire-based measures such as the SARC-F tool to screen those who require further assessment of possible sarcopenia. 27 We found that several common clinical factors such as number of prescribed medications were not associated with prevalent and/or incident sarcopenia. This may be because our study lacked sufficient power to detect such associations.…”
Section: Implications For Clinical Practice and Future Researchmentioning
confidence: 66%